2012
DOI: 10.7341/2012824
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Internet in Overcoming Information Barriers: Implications for Exporting SMEs of the East African Community

Abstract: Small and medium-sized enterprises play a significant role in the East African Community, contributing highly to the national income and employing a significant number of people. Exportation provides a great opportunity for these enterprises to expand their businesses and improve their performance. However, they encounter a number of informationrelated barriers before and during exportation. Based on literature, this paper identifies these barriers and discusses how the internet could be used to reduce them. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Small and medium-sized enterprises (SMEs) are commonly thought of being the key drivers of economic growths in the nations of the world [1]. Over 95% enterprises in the world, for example are SMEs, creating about 60%-70% of the total global jobs [2][3][4]. Because of their importance to economic growths, the crucial question dominating SMEs in the globe is on whether loans infused to them by Microfinance institutions (MFIs) are credible enough to sustainably accelerate their positive growths or not.…”
Section: Background Informationmentioning
confidence: 99%
“…Small and medium-sized enterprises (SMEs) are commonly thought of being the key drivers of economic growths in the nations of the world [1]. Over 95% enterprises in the world, for example are SMEs, creating about 60%-70% of the total global jobs [2][3][4]. Because of their importance to economic growths, the crucial question dominating SMEs in the globe is on whether loans infused to them by Microfinance institutions (MFIs) are credible enough to sustainably accelerate their positive growths or not.…”
Section: Background Informationmentioning
confidence: 99%
“…Factors such as lack of market information, low standard of products produced by the SMEs, lack of knowledge of marketing regulations and standards, lack of consumer needs assessment, weak marketing networking structures and high competition hamper SMEs internationalization (Mbago, 2013;Kazimoto, 2014). Others are lack of information to locate and analyze foreign market, inability to find foreign customers, inability to identify and explore foreign business opportunities, lack of product promotion and inadequate information (Mori & Munisi, 2012).…”
Section: Theme 5 International Marketing Related Constraints and Global Competition (Img)mentioning
confidence: 99%
“…Others are lack of information to locate and analyze foreign market, inability to find foreign customers, inability to identify and explore foreign business opportunities, lack of product promotion and inadequate information (Mori & Munisi, 2012). Trade policies must address issues related to asymmetric information.…”
Section: Figure 3 Framework For Analyzing Sme Participation In Gvcsmentioning
confidence: 99%
“…Results showed that ICT technology adoption is better facilitated in companies that are relatively large, have large human capital, engage in more innovative activities, and align their organizational structure with the given technology in order to maximize the potential. Mori and Munisi (2012) concluded that if SMEs were to use ICT efficiently, their export performance would most likely improve due to specific technology features that empower extension to the international market.…”
Section: Theoretical Backgroundmentioning
confidence: 99%